Perceptions of Tourism Stakeholders towards Tourism Industry in Nepal - Bhote, Gele Rakpe (Journal of Business and Social Sciences Research, 2018)
The main objective of this paper is to study the perceptions of major tourism stakeholders towards the tourism industry of Nepal and how it could be developed holistically. The Primary data was collected by researchers from a convenient sampling of 150 respondents using a structured questionnaire in the year 2014, and was analysed through descriptive and inferential statistics. The perception model for stakeholders was developed considering tourists, tour operators, hoteliers, tourist guides and the host community as the major actors. The study found no significant relationship between stakeholders and their perceptions on; number of stay days, promotional activities done by tourism associations and public agencies, mobilization of tourism revenues, and management and communication of tourism industry. Majority of the respondents perceived future prospects of the tourism industry as favourable. It was found that Nepal could extend tourists’ stays and increase per day spending. Internet was found to be the most reliable source of travel information on Nepal. Political factors scored the highest as an area where major improvements were needed. Tourism revenues were not properly mobilized for the development of the host community. The study concludes that there is a good future for the tourism industry if all stakeholders work cooperatively to solve the major issues that have a negative impact on tourism. Journal of Business and Social Sciences Research, Vol. 1, Issue 1, pp. 129-143